A checklist of vascular plants and uses of some species for livelihood-making in Setiu Wetlands, Terengganu, Malaysia - Jamilah, Mohd Salim; Gaik, Ee Lee; Muhamad Razali, Salam; Salwa, Shahimi; Elizabeth, Pesiu; Jarina, Mohd Jani; Nurul Amira Izzaty, Horsali; Rohani, Shahrudin; Siti Mariam Nor, Muhammad; Ju, Lian Chong; Faridah, Mohamad; Akmal, Raffi; et al. (2020)
The Setiu Wetlands, a unique area with nine interconnected habitats, comprises a considerable fraction of the total Peninsular Malaysia’s wetland flora. Although botanical collecting in the area has been active in the past 10 years, only a few studies dealing with the wetland flora have been published. Thus, a detailed checklist of this area is urgently needed to ensure the continuity of its inter-relating flora and fauna, as well as the livelihood of the local people. In this work we conducted a survey of the vascular plant flora of Setiu Wetlands and investigated the most important plants used by the local communities. Our checklist accounts for 406 taxa from 277 genera and 106 families, including 24 (6%) species of ferns and lycophytes, three gymnosperms, 257 (64%) dicotyledons and 122 (30%) monocotyledons. This comprehensive plant checklist will be a primary reference for the management of the newly gazetted Setiu Wetlands State Park covering more than 400 hectares of lands and water bodies.